Low-frequency measurements of the CMB (cosmic microwave background) spectrum - Kogut, A.; Bensadoun, M.; De Amici, G.; Levin, S.; Limon, M.; Smoot, G.; Sironi, G.; Bersanelli, M.; Bonelli, G. (Lawrence Berkeley Laboratory, 1989)
As part of an extended program to characterize the spectrum of the cosmic microwave background (CMB) at low frequencies, we have performed multiple measurements from a high-altitude site in California. On average, these measurements suggest a CMB temperature slightly lower than measurements at higher frequencies. Atmospheric conditions and the encroachment of civilization are now significant limitations from our present observing site. In November 1989, we will make new measurements from the South Pole Amnudsen-Scott Station at frequencies 0.82 1.5, 2.5, 3.8, 7.5, and 90 GHz. We discuss recent measurements and indicate improvements from a polar observing site. 11 refs., 2 figs.